Optimalisasi Top Schedule dalam Audit: Strategi Penyusunan yang Efektif - Zefania, Anggy; Habibie , Samas Adimisa Mishbah (Lembaga Pengembangan Kinerja Dosen, 2025)
The Top Schedule plays a vital role in the audit process by summarizing the accounts being examined. Despite its importance, the preparation of this document is often hindered by human errors and psychological pressures faced by auditors, such as tight deadlines and fatigue. These challenges can result in inaccurate analysis and delays in audit completion. This study explores the implementation of standardized templates as a strategic approach to enhance the accuracy and consistency of Top Schedule preparation. A consistent format allows auditors to perform their tasks more methodically, thereby minimizing errors in documentation. Furthermore, the research examines how psychological factors influence auditors' attention to detail and how the use of templates can help alleviate these effects. Utilizing a literature review method, this study evaluates the effectiveness of standardized templates. The findings suggest that adopting such templates can significantly reduce human error, improve the efficiency of audit documentation, and streamline the overall audit process.